An empirical study on China's paper industry - Chng, Loi Siang (2014)
Belton M. Fleisher et al’s estimation of the production function of China’s paper industry in his 1993 paper ‘Education, Enterprise Organization and Productivity in the Chinese Paper Industry’ made use of data from 30 firms across China. This project hence examined the accuracy of their estimation in terms of the representativeness of the production function. It is found that the production function estimated by Belton M. Fleisher et al is not representative of the paper industry in terms of average productivity. It only ‘fits’ the firms in their sample. In general the average productivity of labour of the sample firms are higher than the average productivity of the paper industry. In addition, it is found that the increment in marginal productivity of labour of the firms in the sample was not compensated by increment in real wage.